Human-Robot Interaction Perspectives and Applications - Vinjamuri, Ramana (IntechOpen, 2023)
The book Human-Robot Interaction - Perspectives and Applications highlights the latest developments and obstacles in the field of human-machine interaction, including collaborative and humanoid robots, symbiosis between humans and robots, human-human collaboration, and robotics. Human-robot interaction has immense potential in areas like healthcare, education, manufacturing, military, and space exploration. This volume consists of several chapters that explore various topics such as the use of robotic wheelchairs, deep neural networks for robot grasp recognition, materials and sensors required for human-robot interaction, the use of drone technology in agriculture, healthcare robots in smart hospitals, and more.